Key technologies and applications of C-V2X based vehicle-infrastructure cooperative autonomous driving - Kun WANG; Zhenjiang DONG; Fan YANG; Guyue ZHOU (Dianxin kexue)
With the evolution of vehicle-to-everything (V2X) technology, autonomous driving (AD) has entered a new stage of development, called vehicle-infrastructure cooperative autonomous driving (VICAD).Through the integrated complex cyber-physical system formed by the deep integration of “human-vehicle-road-cloud”, cooperative perception, cooperative decision-making and planning, and even cooperative control can be achieved with autonomous vehicles (AV), enhancing the safety of autonomous driving and helping to overcome various complex traffic environments.The concept and overall architecture of the complex cyber-physical system of VICAD was firstly introduced, and a series of typical application scenarios, technical principles, C-V2X performance requirements, and functional and performance requirements of the VICAD system were proposed.It can provide a reference and solution for the deep integration development of intelligent networked vehicles and intelligent transportation in the next stage.